Study On Optimization Of Composite Tubular Energy Absorption System - Sultan Aljibori, Hakim S. (2004)
A four-phase program to improve the specific energy absorbed by axially crushed composite collapsible tubular energy absorber devices was undertaken. In the first phase, the effects of trigged tube wall on the crushing behaviour were investigated. At this stage, triggered tubes were fabricated and crushed. The second phase is aimed at obtaining the best position for the triggered wall. The third phase focuses on the effects of material sizing in order to understand the influence of triggered wall Iength on the responses of composite circular tubes to the axial crushing load. The results from these three phases lead to the fourth phase. The objective of the 4t" phases was to optimise the shape geometry of the cross-section area to further improve tube energy absorption capability. The tubes were manufactured from woven roving glasslepoxy fabric and had the same lay-up providing a common laminate for comparison. The failure modes were observed and the specific sustained crushing loads were determined and compared against non-optimized tubes of the same lay-up. The importance of differentiating between initiation energy and propagation energy is shown, and a new parameter (energy capability index (ECI)) is proposed, as a useful measure for comparing crush behaviour of composite structures. The experimental results demonstrated strong potential benefits of optimizing the material distribution. The sizing and shape optimization of composite collapsible tubes exhibited a pronounced effect on their capability to absorb high specific energy under axial compressive load. For the effect of triggering it was that tubes (TN) observed to experience catastrophic failure mode during the post crush stage also displayed very poor energy absorption. Triggering a part of tube wall was very efficient in improving the energy absorption capacity of circular composite tubes. Accordingly tubes with triggered wall (T-tubes) exhibited highest energy absorption capacity compared with non-triggered tubes. They also experience stable post-crush region of loaddisplacement curves, which leads to high crashworthiness performance. It is also evident from the experimental results that change in the triggered wall aspect ratio significantly affected the energy absorption capability of tube with middle triggered wall (TM-tubes). Distinct differences were observed between the different aspect ratio, where TM tubes (i.e. tubes with triggered wall aspect ratio of 0.28) exhibited the highest energy absorption capacity. Different failure modes were observed for different triggered wall length ratios (Lt,/H). For the core tubes (TMC-), was observed that core presence markedly improved the energy absorption capacity of composite circular tubes. Among TMC- tubes, TMC3 tubes (i.e. tubes with core thickness of 3.35mm) displayed highest energy absorption capacity.